Study the Different Concentrations of Hydrochloric and Sulphuric Acid as Dopants For Polyaniline - Mohd Najib, Nur ‘Izqa Ashiqin; Othman, Siti Amira (Journal of Science and Technology, 2022)
Conducting polymers have previously been employed in biosensors because they may be used as immobilisation matrices as well as redox systems. Also have numerous uses in medical, pharmacy, environmental monitoring, food and process control. The conductivity of polyaniline-based compositions may be precisely regulated over a broad range. Polyaniline is ease to synthesis, has high conductivity and good performance in biosensor applications. However, polyaniline is not entirely perfect because of its poor solubility in many solvents and low adhesion to different substrate. In this study, hydrochloric acid (HCl) and sulphuric acid (H2SO4) were prepared with different concentration (0.2M, 0.4M, 0.6M, 0.8, 1.0M) for doping process of polyaniline. Fourier-transform Spectroscopy (FTIR), Ultraviolet Spectroscopy (UV-Vis) and Scanning Electron Microscopy (SEM) were used to characterize the properties and morphology of the polyaniline. Four point probe was used to identify the conductivity of the polyaniline sample. FTIR shows a shift peak at benzenoid rings and quioniod rings. Both acids represent that 1.0 M have high absorbance properties. While SEM shows significant different of agglomeration rate for HCl compared to H2SO4. Lastly, the results showed that the conductivity increasing when the concentration of acids increasing. Doping process helps in enhancing the conductivity properties of polyaniline for biosensor application.